Tools and techniques for the static verification of progress in communication-centred systems - Camacho, André Filipe Marinhas Henriques da Silva (2014)
Tese de mestrado, Engenharia Informática (Engenharia de Software), Universidade de Lisboa, Faculdade de Ciências, 2014